2008
DOI: 10.1159/000183754
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Clinical Features of ANCA-Positive and ANCA-Negative Idiopathic Pulmonary Fibrosis Patients

Abstract: Background: The existence of antineutrophil cytoplasmic antibody (ANCA)-positive pulmonary fibrosis (PF) has recently been recognized. Objectives: The aim of this study was to clarify whether there is any difference in the clinical features between ANCA-positive PF and ANCA-negative PF. Methods: A retrospective study was carried out on 53 patients with idiopathic PF whose myeloperoxidase (MPO)- and proteinase 3 (PR3)-ANCA levels were measured. After dividing the patients into ANCA-positive and ANCA-negative PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
80
1
20

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 52 publications
6
80
1
20
Order By: Relevance
“…Pulmonary fibrosis is also a potentially severe manifestation of MPA, but mild pulmonary fibrosis is significantly associated with an increased rate of mortality [2][3][4]. Although pulmonary fibrosis in MPA might result from iterative episodes of alveolar haemorrhage, half of patients with pulmonary fibrosis have no history of haemoptysis and pulmonary fibrosis can be the initial manifestation of the disease, sometimes several years prior to the diagnosis of MPA [2,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary fibrosis is also a potentially severe manifestation of MPA, but mild pulmonary fibrosis is significantly associated with an increased rate of mortality [2][3][4]. Although pulmonary fibrosis in MPA might result from iterative episodes of alveolar haemorrhage, half of patients with pulmonary fibrosis have no history of haemoptysis and pulmonary fibrosis can be the initial manifestation of the disease, sometimes several years prior to the diagnosis of MPA [2,5].…”
mentioning
confidence: 99%
“…In MPA, ANCAs exhibit mainly a perinuclear fluorescent pattern and are directed to myeloperoxidase (MPO). Although anti-MPO antibodies (Abs) are associated with pulmonary fibrosis [2,5], their role in this pathophysiological process has been poorly understood so far.…”
mentioning
confidence: 99%
“…Here, we report two cases in which p-ANCA was negative at the time of diagnosis of pulmonary fibrosis and became positive during follow-up, predating the onset of fulminant vasculitis. There are no reported differences in the clinical or radio graphical characteristics of p-ANCA positive as compared to p-ANCA negative pulmonary fibrosis at the time of initial diagnosis [3]. However, in the presence of p-ANCA positivity, the clinical course of the disease may be affected, with increased morbidity and mortality observed [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with initial diagnosis of PF, occasionally acquire seropositivity for MPO-ANCA, which may develop to microscopic polyangitis (MPA) (Ando et al 2013). The prevalence of ANCA in patients with ILD in literature is suggested at 8-36% (Nozu et al 2009;Foulon et al 2008). Homma et al showed positive ANCA as an unfavorable prognostic factor in patients with pulmonary fibrosis (Homma et al 2004).…”
Section: Pulmonary Fibrosis and Anca Positivitymentioning
confidence: 99%
“…Homma et al showed positive ANCA as an unfavorable prognostic factor in patients with pulmonary fibrosis (Homma et al 2004). Nozu et al demonstrated that a high titer of ANCA is associated with a poor prognosis and higher risk for progression to MPA (Nozu et al 2009). In fact, in a study by Foulan et al, 41% of patients with PF and ANCA positivity developed MPA over time (Foulon et al 2008).…”
Section: Pulmonary Fibrosis and Anca Positivitymentioning
confidence: 99%